Informatization of the processes of administration of the quality of medical services in surgical hospitals - Ya.S. Bereznytskyi; V.Ya. Bereznytskyi; O.V. Hudoshyna; N.D. Chuhrienko; G.V. Bereznytska; Ye.V. Zalyhina; Yu.B. Dianova; E.A. Rynska; L.N. Ksykevich (Medičnì Perspektivi)
Among the various forms of quality control of the provision of medical care, self-control and internal control of the quality of medical services are the most effective and significant. Currently, there is no comprehensive information technology and algorithm for recording data on the provision of medical services and determining their quality. The goal is to develop and analyze the effectiveness of business processes and an algorithm for quality control of the performance of medical services in a surgical health care institution by establishing their daily accounting in the information system, control of indicators characterizing the safety and quality of their performance, as well as an opportunity to assess the dynamics changes in indicators for making management decisions. In the study, an analysis of literary sources was carried out, business processes were formulated, and on the materials of a retrospective analysis algorithms for the use of information technologies were developed based on the methods of generalization, comparison, content analysis, system-analytical and logical analysis, a graphic analysis was performed to increase the clarity of the presentation of the material. The research was approved by the Biomedical Ethics Committee. For the first time, as a result of the work of the internal quality commission, daily and summarized forms of reports on the work of the medical center, which have five sections are obtained. The statistical indicators of the operation of the surgical unit for any period are fixed, formed in an automated mode and analyzed. Clinical data characterizing all prescribed procedures applied are subject to analysis, and the results provide an opportunity to isolate from the records the disorders and complications reflected in the reports. The quality control of the use of antibiotics, the frequency of their use for preventive and therapeutic purposes is also carried out. The section that contains multivariate epidemiological control of the work of the treatment facility, as well as the section that shows the quality of medical record keeping and patient care is important. Together with the inpatient chart, e-mails of medical appointments are analyzed, patient falls are recorded, appointments and monitoring of patient care, pain assessment after surgery, allergic reactions are recorded, as well as a retrospective audit of the charts regarding the justification of the appointment of antimicrobial therapy. Control of patient safety and the quality of the provided medical services requires constant verification of their implementation and paying attention to be up to standards, the occurrence of deviations and complications. The application of a specially developed algorithm based on information technologies, aimed at daily accounting of medical services and obtaining data on deviations in their application, makes it possible to make urgent management decisions and influence the improvement of the qualifications of personnel who provide such services.